2010
DOI: 10.1055/s-0030-1268472
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptual Responses to Occluded Exercise

Abstract: The purpose was to determine repetitions to failure and perceptual responses to exercise with and without occlusion. 15 subjects participated in a randomized crossover study of 3 trials. The first determined one repetition maximum (1RM) on the leg extension. Subjects were then assigned to an occlusion (OCC) or control (CON) group. After trial 2, subjects crossed over to the opposite trial. Knee wraps (KW) were placed around the upper thigh of each leg during OCC. Subjects completed 2 sets of leg extensions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 16 publications
4
59
0
1
Order By: Relevance
“…Studies by Hollander et al 31,32 found that, though RPE is typically reported as being higher than discomfort (the authors used the term pain) for a range of RT conditions (different loads and contraction types), both respond in a similar fashion. Studies using blood flow restriction based RT have shown similar findings 33,34 , though it should perhaps be noted that this unique form of exercise typically produces greater discomfort post completion (i.e. during the rest periods).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Studies by Hollander et al 31,32 found that, though RPE is typically reported as being higher than discomfort (the authors used the term pain) for a range of RT conditions (different loads and contraction types), both respond in a similar fashion. Studies using blood flow restriction based RT have shown similar findings 33,34 , though it should perhaps be noted that this unique form of exercise typically produces greater discomfort post completion (i.e. during the rest periods).…”
Section: Introductionmentioning
confidence: 85%
“…19,[23][24][25] Certain manipulations of RT variables appear to have the potential to impact upon RPE in unexpected ways and thus may indicate a conflation of perceived effort and discomfort by participants. [26][27][28][29][30] Indeed, even where studies have attempted to differentiate the two, strong relationships in their responses manifest both during traditional RT and blood flow restriction based RT [31][32][33][34] . This may be potentially be due to these studies in some cases using high effort RT conditions known also to anecdotally produce high levels of discomfort (e.g.…”
Section: Figure 3 Scatter Plot Of Rpe-e and Rpe-d For Combined Datamentioning
confidence: 99%
“…In addition, significant gains in muscle size and strength with aerobic walking BFRE have also been reported (Abe et al 2006;Sakamaki et al 2011). While these gains in muscle size and strength have largely been the primary focus of interventional studies of BFRE (Abe et al 2005(Abe et al , 2006Yasuda et al 2011;Karabulut et al 2010), the acute haemodynamic and perceptual responses to BFRE are less well characterised (Hollander et al 2010;Loenneke et al 2011;Vieira et al 2013). These would, however, seem essential to evaluate if BFRE is to be more widely prescribed.…”
Section: Introductionmentioning
confidence: 99%
“…This is despite these muscle groups being used frequently in older adults for mobility, activities of daily living and exercise. Similarly, while perceptual responses have been examined for resistance BFRE (Hollander et al 2010;Lagally et al 2002;Loenneke et al 2011), little is known for aerobic BFRE, with no study comparing these responses between young and older adults despite being relevant to further understanding exercise tolerance and programme adherence (Loenneke et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…24 Interestingly, although the BFR is limited to the limbs, favorable adaptations have also been observed the trunk, which is proximal to the BFR stimulus. 25 A variety of devices have been used to restrict blood flow during exercise including elastic knee wraps, 26 elastic belts with a pneumatic bag inside, 27 nylon pneumatic cuffs, 28 or a traditional nylon blood pressure cuff 29 . A recent Meta-Analysis of BFR training suggests that this type of training produces skeletal muscle adaptation similar to that observed with higher load (>60% concentric 1RM) resistance exercise, 30 however the exact mechanisms behind the benefits observed with this mode of training are largely unknown 31 .…”
Section: Effect Of Blood Flow Restricted Exercisementioning
confidence: 99%